2007
DOI: 10.1136/jcp.2007.047134
|View full text |Cite
|
Sign up to set email alerts
|

Chronic atrial fibrillation associated with somatic mitochondrial DNA mutations in human atrial tissue

Abstract: premature stop codon 91 amino acids downstream from the last original amino acid (Ala 227). This mutation resulted in the subsequent generation of a non-functional short polypeptide (318 amino acids) that lacks its intracellular C-terminal region or well in a null allele. In this region, URAT1 directly interacts with PDZK1, a PDZ domain-containing protein that interacts with several membrane proteins through its PDZ motif.11 PDZK1 regulates the functional activity of URAT1-mediated urate transport in the apica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…35 On the other hand, AF patients have increased mtDNA mutation rates and evidence of atrial oxidative injury. 36 In patients undergoing cardiac surgery (22 children/adolescents and 66 adults), mtDNA deletions were increased in the adult AF patients compared with those in sinus rhythm. Pediatric and adolescent patients did not show mtDNA deletions; thus, mtDNA deletion seems to be associated with aging.…”
Section: Mitochondrial Dysfunction and Ros Generationmentioning
confidence: 99%
“…35 On the other hand, AF patients have increased mtDNA mutation rates and evidence of atrial oxidative injury. 36 In patients undergoing cardiac surgery (22 children/adolescents and 66 adults), mtDNA deletions were increased in the adult AF patients compared with those in sinus rhythm. Pediatric and adolescent patients did not show mtDNA deletions; thus, mtDNA deletion seems to be associated with aging.…”
Section: Mitochondrial Dysfunction and Ros Generationmentioning
confidence: 99%
“…Thanks to a remarkable resequencing effort in selected cohorts, at least 12 ion channels (alpha and beta subunits) and 3 nonion channels genes causing or predisposing to AF have been identified. Furthermore, GWAS studies demonstrated the existence of multiple AF risk loci (>10) and mitochondrial DNA mutations have been found to have a causative role in some cases . However, it is also true that the identification of families in which AF is indisputably distributed in a Mendelian fashion is rare, and cohort molecular screening studies have identified mutation only in a small fraction of cases with limited clinical implications …”
Section: Editorial Commentmentioning
confidence: 99%
“…Furthermore, GWAS studies demonstrated the existence of multiple AF risk loci (>10) 6 and mitochondrial DNA mutations have been found to have a causative role in some cases. 7,8 However, it is also true that the identification of families in which AF is indisputably distributed in a Mendelian fashion is rare, and cohort molecular screening studies have identified mutation only in a small fraction of cases with limited clinical implications. 9 So there is a clear discrepancy between the richness of identified genetic causes and the power of genetic testing to identify successfully the genetic defect when the screening is "clinically driven."…”
Section: Considerations On Genetic Epidemiology Of Afmentioning
confidence: 99%
“…The displacement loop (D-loop) region is the major control site for mtDNA replication and transcription (3). The D-loop region is increasingly susceptible to oxidative damage and electrophilic attack (4,5), thus it is more prone to mutation. It has been acknowledged that exercise causes an increase in the skeletal muscle mitochondrial enzyme content and activity (6).…”
Section: Introductionmentioning
confidence: 99%
“…It has been acknowledged that exercise causes an increase in the skeletal muscle mitochondrial enzyme content and activity (6). Perturbations in mitochondrial content and function have been linked to a wide variety of diseases in multiple tissues, and exercise may serve as a potent approach by which to prevent and treat these pathologies (5). However, no study has been conducted to evaluate the association effects of exercise on mtDNA content and mutations.…”
Section: Introductionmentioning
confidence: 99%